Frequency and predictors of depression and anxiety in chronic illnesses: A multi disease study across non-communicable and communicable diseases - Uzair Abbas; Niaz Hussain; Misha Tanveer; Rabeel Nawaz Laghari; Ishfaque Ahmed; Ali Bux Rajper (PLoS ONE, 2025)
Background Depression and anxiety are among the most common mental health conditions globally that impact the lifestyle of affected individuals. Mental conditions and chronic diseases are linked to each other bidirectionally. Depression and anxiety with comorbid chronic conditions are often neglected or under-screened and possess challenges in treatment. This study aimed to know the frequency and determinants of depression and anxiety along with the severity level among common chronic communicable and non-communicable diseases. Methods We enrolled 200 healthy controls and 800 cases with equal number (n = 400) of patients with communicable and non-communicable diseases. Depression and anxiety were screened through Hamilton’s rating scale for depression and anxiety separately. We also measured the determinants of severe depression among patients with chronic diseases. Data was analyzed through SPSS version 23. Results We found higher frequency of depression (31% vs 11%; p=<0.001) and anxiety (13.25% vs 6%; p = 0.021) among cases as compared to healthy controls respectively. We found higher levels of depression among participants with non-communicable diseases as compared to communicable diseases (37.25% vs 24.75%; p < 0.05) respectively. Moreover, there was a higher frequency of anxiety in participants with communicable diseases as compared to those with non-communicable diseases, but the difference was non-significant (14% vs 12.5% p = 0.081). Among non-communicable diseases the highest percentage was found among individuals with cancer (67%), followed by diabetes (38%), cardiovascular diseases (33%) and respiratory disorders (11%). Among participants with communicable diseases, the highest percentage of depression was found in patients with Tuberculosis (29%) followed by HIV/AIDS (28%), Long COVID-19 (25%) and Hepatitis B/C (17%). Conclusion There is a significantly higher percentage of depression and anxiety among participants with chronic diseases. It calls for a comprehensive approach to patient care that incorporates mental health as a fundamental aspect of the treatment and management of chronic diseases. Understanding the predictors of severe depression across different chronic conditions helps in stratifying patients who may benefit most from integrated psychiatric and psychological interventions.